Factors associated with psychological distress among young women in Kisumu, Kenya - Gust DA; Gvetadze R; Furtado M; Makanga M; Akelo V; Ondenge K; Nyagol B; McLellan-Lemal E (Dove Medical Press, 2017)
Deborah A Gust,1 Roman Gvetadze,1 Melissa Furtado,2 Mumbi Makanga,3 Victor Akelo,3 Kenneth Ondenge,3 Beatrice Nyagol,3 Eleanor McLellan-Lemal11Division of HIV/AIDS Prevention, Centers for Disease Control and Prevention, 2Engility Corporation, Atlanta, GA, USA; 3HIV Research Branch, Kenya Medical Research Institute, Kisumu, KenyaBackground: Attention to mental health issues is growing globally. In many countries, including Kenya, however, assessment of psychological distress, especially in rural areas, is limited.Methods: We analyzed data from young women screened for a longitudinal contraceptive ring study in Kisumu, Kenya. Multivariable regression analysis was used to assess factors associated with recent moderate and high psychological distress, as measured by the Kessler (K-6) psychological distress scale.Results: Among the 461 women screened, most (58.4%) were categorized as having moderate psychological distress, 20.8% were categorized as having low or no psychological distress, and 20.8% were categorized as having high psychological distress. Moderate psychological distress (vs low/no) was significantly more likely among women who reported a history of forced sex and were concerned about recent food insecurity. High (vs low/no) psychological distress was significantly more likely among women who reported a history of forced sex, who were concerned about recent food insecurity, and who self-reported a sexually transmitted infection.Conclusion: To reduce psychological distress, a focus on prevention as well as care methods is needed. Girls need a path toward a healthy and productive adulthood with a focus on education, which would help them gain skills to avoid forced sex. Women would benefit from easy access to social services and supports that would help them with basic needs like food security among other things. A holistic or ecological approach to services that would address mental, educational, social, health, and economic issues may have the highest chance of having a long-term positive impact on public health. Keywords: forced sex, food insecurity, HIV, holistic